Disparities in hepatitis A virus (HAV) vaccination coverage among adult travelers to intermediate or high-risk countries: The role of birthplace and race/ethnicity. Issue 30 (9th July 2019) - Narayanan, Navaneeth; Elsaid, Mohamed I.; NeMoyer, Rachel E.; Trivedi, Niti; Zeb, Uroosa; Rustgi, Vinod K.
Abstract: Background: While the hepatitis A virus (HAV) vaccine is recommended for United States (US) travelers to endemic regions, vaccination rates are lower among non-US-born adults and some racial minority groups. Purpose: We aimed to examine the relationship between birthplace, race and their interaction as predictors of self-reported HAV vaccination among adult travelers to high-risk countries (HRCs) through analysis of the National Health Interview Survey (NHIS), 2012–2015. Methods: The study included 36, 872 US adult participants in the 2012–2015 NHIS who traveled to countries where HAV is endemic. The main outcome was self-reported HAV vaccination (≥2 doses). Complex survey methods were applied to all models to provide statistical estimates that were representative of US adults. Multivariable logistic regression models adjusting for demographic, socioeconomic, medical, and access-to-care characteristics were fitted to examine the association between birthplace, race, race-by-birthplace (for interaction) and vaccination status. Results: For adult travelers to HRCs, the adjusted odds ratio (AOR) of HAV vaccination was lower for non-US-born compared to US-born adults, AOR 0.86 (95% CI; 0.76, 0.98). For Hispanics, the AOR of HAV vaccination was 0.80 (95% CI; 0.70, 0.91) as compared to non-Hispanic-Whites. Furthermore, a significant qualitative interaction between birthplace and race was found (P-value 0.0005). Among non-Hispanic Blacks, the adjusted odds of HAV vaccination for non-US-born adults were 1.35 (95% CI; 1.06, 1.72) times the odds for US-born adults. In contrast, the AORs of HAV vaccination of non-US-born versus US-born adults were 36% (95% CI; 17%, 51%) and 30% (95% CI; 12%, 44%), lower for Asians and Hispanics, respectively. Conclusions: The association between birthplace and HAV vaccination status differs by race among travelers to HRCs, with US-born non-Hispanic Black and non-US-born Asian and Hispanic adults having lower odds of vaccination. Health care resources should be focused on these target populations to improve travel vaccination compliance.